A Dynamic Model of the Racial Wealth Gap - Catherine, Sylvain; Lu, Ellen Jiayang; Paron, James D (Review of Financial Studies, 2026)
What explains wealth and portfolio differences between black and white Americans? We find that disparities in economic factors explain portfolios well, but only partly explain the wealth gap. In a dynamic setting, economic factors often change optimal saving rates in ways that offset their effects on income and returns. Consequently, their net wealth effect is often limited, making the wealth gap harder to explain. We estimate that differences in income levels, income risk, family structures, mortality, health expenditures, property taxes, mortgage rates, and asset returns explain half of the differential between the racial wealth gap and the racial income gap.